Enhancing Accountability Mechanisms in NGT: Constitutional and Legisla tive Reforms - Gupta, Shivangi (Trinity Law Review, 2025)
The National Green Tribunal (NGT) was established as a specialized body to address environmental disputes and ensure the effective enforcement of environmental laws in India. However, challenges related to accountability and execution have often impeded its ability to function optimally. This paper examines the accountability mechanisms of the NGT within the framework of India’s constitutional provisions and statutory mandates. It highlights the gaps in its current regulatory and enforcement structures that hinder effective environmental governance. The study explores relevant constitutional principles, such as the directive under Article 48A to protect and improve the environment and the fundamental duty under Article 51A(g) to safeguard natural resources. Additionally, it critically evaluates the NGT’s quasi-judicial status and the limitations imposed by legislative ambiguities and inadequate administrative support. The paper proposes constitutional and legislative reforms, including amendments to enhance the NGT’s powers for monitoring compliance, increasing transparency and ensuring judicial review of its decisions. By strengthening accountability mechanisms, the NGT can emerge as a more robust institution capable of upholding environmental justice and addressing pressing ecological concerns.